Challenges experienced by U.S. K-12 public schools in serving students with special education needs or underlying health conditions during the COVID-19 pandemic and strategies for improved accessibility. Issue 2 (April 2023) - Spencer, Patricia; Timpe, Zach; Verlenden, Jorge; Rasberry, Catherine N.; Moore, Shamia; Yeargin-Allsopp, Marshalyn; Claussen, Angelika H.; Lee, Sarah; Murray, Colleen; Tripathi, Tasneem; Conklin, Sarah; Iachan, Ronaldo; et al.
Abstract: Background: Students with special education needs or underlying health conditions have been disproportionately impacted (e.g., by reduced access to services) throughout the COVID-19 pandemic. Objective: This study describes challenges reported by schools in providing services and supports to students with special education needs or underlying health conditions and describes schools' use of accessible communication strategies for COVID-19 prevention. Methods: This study analyzes survey data from a nationally representative sample of U.S. K-12 public schools (n = 420, February–March 2022). Weighted prevalence estimates of challenges in serving students with special education needs or underlying health conditions and use of accessible communication strategies are presented. Differences by school locale (city/suburb vs. town/rural) are examined using chi-square tests. Results: The two most frequently reported school-based challenges were staff shortages (51.3%) and student compliance with prevention strategies (32.4%), and the two most frequently reported home-based challenges were the lack of learning partners at home (25.5%) and lack of digital literacy among students' families (21.4%). A minority of schools reported using accessible communications strategies for COVID-19 prevention efforts, such as low-literacy materials (7.3%) and transcripts that accompany podcasts or videos (6.7%). Town/rural schools were more likely to report non-existent or insufficient access to the internet at home and less likely to report use of certain accessible communication than city/suburb schools. Conclusion: Schools might need additional supports to address challenges in serving students with special education needs or with underlying health conditions and improve use of accessible communication strategies for COVID-19 and other infectious disease prevention.